The cultural repertoire of recontextualized superhero in the Avengers sequels - Musrifatun Nangimah (Universitas Islam Sultan Agung, 2021)
This research presents content analysis to the cultural repertoire of Marvel Cinematic Universe’s superhero motion pictures. It investigates the content, theme, and core ideas of Avengers sequels: The Avengers (2012), Avengers: Age of Ultron (2015), Avengers: Infinity War (2018), and Avengers: Endgame (2019). It explores how the Avengers sequels portrays recontextualization of superhero characters and whether as well as to what extent it provides US cultural monomyth. The finding shows that each character of the Avengers has flaws and vulnerabilities as common human beings that leave them from traditional superhero monomyth. Nevertheless, it still illustrates US cultural imperialism, pharmakon portrayal, hegemonic masculinity, and sovereignty. These motion pictures still serve US heroism and patriotism interest as well as binary interplay: order-chaos, law-violence and villain-superhero that occurs among superheroes, extra-terrestrial race, robots and Titans despite its recontextualized characters. Moreover, it depicts the traditional masculine ideal valorisation where men are more likely powerful, intelligent, and equipped by sophisticated technology whereas women are seen as supportive superheroes with implied beauty standards. The recommendation for future research is discussed.